1998
DOI: 10.1073/pnas.95.16.9705
|View full text |Cite
|
Sign up to set email alerts
|

Directed disruption of the tobacco ndhB gene impairs cyclic electron flow around photosystem I

Abstract: To evaluate the physiological significance of cyclic electron f low around photosystem (PS) I, we used a reverse genetic approach to focus on 11 chloroplast genes that encode homologs of mitochondrial complex I subunits (ndhA-K). Since their discovery, the exact function of the respiratory components in plant chloroplasts has been a matter of discussion. We disrupted one of these genes (ndhB) in tobacco by chloroplast transformation. Analysis of the transient increase in chlorophyll f luorescence after actinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
356
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(394 citation statements)
references
References 27 publications
24
356
1
1
Order By: Relevance
“…In the WT, a transient increase in the fluorescence level was observed before reaching the F 0 level, this effect being absent in ndhB Ϫ . This confirms recent work reporting that the postillumination fluorescence rise is absent in ndh inactivated mutants (Burrows et al, 1998;Cournac et al, 1998;Kofer et al, 1998;Shikanai et al, 1998). Figure 2A shows that qP rapidly increased during the first 2 min of illumination in both WT and ndhB Ϫ before reaching progressively a plateau.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In the WT, a transient increase in the fluorescence level was observed before reaching the F 0 level, this effect being absent in ndhB Ϫ . This confirms recent work reporting that the postillumination fluorescence rise is absent in ndh inactivated mutants (Burrows et al, 1998;Cournac et al, 1998;Kofer et al, 1998;Shikanai et al, 1998). Figure 2A shows that qP rapidly increased during the first 2 min of illumination in both WT and ndhB Ϫ before reaching progressively a plateau.…”
Section: Resultssupporting
confidence: 79%
“…More recently, based on P700 ϩ rereduction measurements performed in barley thylakoids, Scheller (1996) proposed the existence of an antimycin-insensitive cyclic electron transport around PSI. The involvement of the NDH complex in cyclic electron flow in association with other pathways was shown in cyanobacteria (Mi et al, 1992;Yu et al, 1993) and recently suggested in higher plants from in vitro experiments performed on broken chloroplasts (Endo et al, 1998). Based on a differential sensitivity to antimycin A of PQ reduction in the WT and in a ndhB Ϫ mutant, these authors concluded to the existence of two pathways, one of them involving the NDH complex.…”
Section: Involvement Of the Ndh Complex In Cyclic Electron Flow Arounmentioning
confidence: 94%
See 2 more Smart Citations
“…In cyclic electron transfer, electrons can be recycled from reduced ferredoxin or NADPH either directly to plastoquinone (Clark et al, 1984;Zhang et al, 2001), or alternatively via the type I NAD(P)H dehydrogenase (NDH-1) complex to plastoquinone and subsequently to the cytochrome (cyt)-b 6 f complex. The latter route is known to be involved in dark reduction of the plastoquinone pool (Burrows et al, 1998;Joet et al, 2001;Kofer et al, 1998;Shikanai et al, 1998). The change in pH (DpH) generated by cyclic electron transfer is important for production of ATP, but also for the induction of thermal dissipation of absorbed energy from PSII antennae (Johnson, 2005).…”
Section: Introductionmentioning
confidence: 99%